Curvas de referência para o índice de performance miocárdica e Doppler tecidual e suas aplicabilidades em fetos de gestantes diabéticas tipo I e II. - Peixoto, Alberto Borges [UNIFESP] (2019)
Objectives: to estabilish reference ranges for myocardial performance index using tissue Doppler (MPI) and spectral Doppler (MPI), peak flow velocity during the passive (E wave) and active (wave A) phases through the valves mitral and tricuspid, using spectral Doppler and annular peak velocity (APV) of the right ventricles (RV) and left ventricle (LV). To evaluate inter and intraobserver reproducibility. To evaluate the effect of type I (DM I) and type II diabetes mellitus (DM II) on the parameters of fetal heart function. Methods: A cross-sectional study was conducted evaluating 403 pregnant women divided into three groups: 360 normal (control group), 23 with type I diabetes and 20 with type II diabetes with body mass index (BMI) ≤ 35 kg / m2 and gestational age between 20 and 36 + 6 weeks. The MPI using spectral and tissue Doppler was calculated using the following formula: (isovolumetric contraction time + isovolumetric relaxation time) / ejection time. The peak velocity of the E and A waves were performed by positioning the sample volume just below the mitral and tricuspid valves. The APV during systole (S '), beginning (E') and end of diastole (A') were performed with the sample volume placed in the basal segment of the lateral wall of the right (RV) and left ventricle (LV). Polynomial regression was used to obtain the best fit for the parameters of cardiac function and gestational age (GA) with adjustments using the coefficient of determination (R2). The percentiles 5th, 50th and 95th of the cardiac function evaluation parameters were determined for each gestational age. To evaluate the effect of DM I and DM II on fetal heart function, the Kruskal-Wallis test was used. The post hoc analises using the Dunn’s test was used to comparison between pairs that presented significant difference. Results: LV MPI (p = 0.002) and isovolumetric relaxation time (IRT) (p < 0.001) significantly increased with advancing GA. Isovolumetric contraction time (ICT) and ejection time (ET) did not significantly change with GA. RV and LV E wave, A wave, and E/A ratio significantly increased with GA (p < 0.001). Only LV A wave measurements demonstrated an intra-observer CCC > 0.80. The remaining intra- and inter-observer reproducibility parameters demonstrated lower CCC. All MTD velocities (cm/s) progressively increased with advancing GA (p<0.0001). The following parameters have had significant decrease with GA: transtricuspid diastolic velocity / annular tricuspid velocity (RV E/E'), xxii transmitral diastolic velocity / annular mitral velocity (LV E/E’). LV MPI’, RV MPI’ did not significantly change with advancing GA. The CCC values for MTD were predominantly greater than 0.70, while those for MPI’ were < 0.70. In patients with DM 1, we observed an increase in the measures that evaluate the LV diastolic function (LV A, LV IRT`, LV MPI`), a decrease in the parameters that evaluate the LV systolic function (RV TE`) and increase the parameters that evaluate the diastolic function of the RV (RV IRT`). In patients with DM II, we observed an increase in the parameters that evaluate the LV diastolic function (LV A, LV MPI, LV E`, LV A`, LV IRT`), decrease in the parameters that evaluate the LV systolic function (LV ET), increase in the parameters that evaluate the RV diastolic function (RV MPI`), increase in the parameters that evaluate the RV systolic function (RV S`). Conclusion: reference ranges were determined for parameters of fetal cardiac function using conventional spectral Doppler and tissue Doppler. The vast majority of fetal cardiac function parameters tested did not demonstrate good / moderate intra and interobserver reproducibility. The results presented in our study reinforce the possibility of common coexistence of diastolic and subclinical biventricular systolic dysfunction in patients with pre-gestational diabetes, but it was not possible to determine a characteristic pattern of cardiac function-specific alteration for each of these conditions.